Stanovenie imunosupresívnych liečiv pomocou LC/MS-MS - Valachovičová, Martina; Príbojová, Jana; Mišľanová, Csilla (Chemické listy, 2021)
In Slovakia, approximately 200 kidneys are transplanted annually. Each patient-recipient must be adjusted to the most appropriate immunosuppressive treatment to eliminate renal rejection. The high-performance liquid chromatography connected to tandem mass spectrometry was validated for the determination of cyclosporine A, tacrolimus, sirolimus, and everolimus in the whole blood. For the determination, C18 analytical column with a gradient of 10 mmol/L ammonium acetate, pH 4.0 and acetonitrile was used. A simple protein precipitation with zinc sulphate: methanol was used for the pretreatment of whole blood. The method provides reliable and reproducible results and it can be introduced to routine clinical practice.